Selection and Validation of Reference Genes For qRT-PCR Analysis of Rhopalosiphum padi (Hemiptera: Aphididae) - Li, Mengyi; Li, Xinan; Wang, Chao; Li, Qiuchi; Zhu, Saige; Zhang, Yunhui; Li, Xiangrui; Yang, Fengshan; Zhu, Xun (Frontiers in Physiology, 2021)
Rhopalosiphum padi (L.) (Hemiptera: Aphididae) is an important cosmopolitan pest in cereal crops. Reference genes can significantly affect qRT-PCR results. Therefore, selecting appropriate reference genes is a key prerequisite for qRT-PCR analyses. This study was conducted to identify suitable qRT-PCR reference genes in R. padi. We systematically analyzed the expression profiles of 11 commonly used reference genes. The ΔCt method, the BestKeeper, NormFinder, geNorm algorithms, and the RefFinder online tool were used to evaluate the suitability of these genes under diverse experimental conditions. The data indicated that the most appropriate sets of reference genes were β-actin and GAPDH (for developmental stages), AK and TATA (for populations), RPS18 and RPL13 (for tissues), TATA and GAPDH (for wing dimorphism), EF-1α and RPS6 (for antibiotic treatments), GAPDH and β-actin (for insecticide treatments), GAPDH, TATA, and RPS18 (for starvation-induced stress), TATA, RPS6, and AK (for temperatures), and TATA and GAPDH (for all conditions). Our study findings, which revealed the reference genes suitable for various experimental conditions, will facilitate the standardization of qRT-PCR programs, while also improving the accuracy of qRT-PCR analyses, with implications for future research on R. padi gene functions.